Factors affecting production of quality grapes (Vitis vinifera) for domestic and export market: a review - Somkuwar, R G; Rutuja Nale (Current Horticulture, 2025)
Grape (Vitis vinifera L.) cultivars and hybrids of V. vinifera with V. labrusca L. and V. amurensis Rupr.) belonging to Vitaceae family of deciduous woody perennials are most widely consumed non-climacteric fruits globally. In India, table grapes are gaining popularity due to its various attributes and availability of nutritional compounds. The grape quality refers to various attributes, including appearance, colour, texture, flavour, and aroma. The ripening process begins at the veraison stage, marked by sugar accumulation, berry softening, anthocyanin production, metabolism of organic acids, and build-up of flavour compounds. The present review explores a wide range of factors that influence grape quality. The impact of cultural operations such as leaf removal, cluster thinning, shoot pinching, use of plant growth regulators and training system are of vital importance. The effect of temperature, light, water availability and rootstocks on grape quality are summarized.